Analisis Yuridis terhadap Penetapan Anak Laki-Laki dari Saudara Kandung Perempuan yang Meninggal Terlebih Dahulu sebagai Penerima Wasiat Wajibah - Muhammad Salman Pauzi; Eneng Nuraeni; Aziz Sholeh (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2026)
This study aims to analyze the legal basis for determining the sons of deceased siblings as recipients of wajibah wills in Decision Number 285/Pdt.P/2025/PA.Sbg, and to assess its compliance with the principles of Islamic inheritance law and positive legal provisions in Indonesia. The method used is a content analysis method with a normative juridical research approach, including a statutory approach, supported by a descriptive analysis of the judge's considerations (ratio decidendi) in the decision. The results of the study indicate that the judge did not conduct an extensive interpretation in determining all children of deceased siblings as recipients of wajibah wills based on the principles of justice and benefit in order to provide protection to parties who do not directly receive a share of the inheritance. However, this determination does not have an explicit regulatory basis in either the Compilation of Islamic Law or the SEMA. Thus, it has the potential to create legal uncertainty and disparity in decisions within the religious courts. Therefore, it is necessary to strengthen the normative basis and clearer judicial guidelines to ensure consistent application of the law and a balance between substantive justice and legal certainty.